Vad ska chatta heta på finska? Efcot-projektet, att bygga upp ett europeiskt forum för dataterminologi - Holmér, Åsa (Nordiske Studier i Leksikografi, 2001)
In Sweden today almost everyone comes into contact with computers. However, when speaking or writing about computers, English terms are often used for lack of Swedish ones. In order to give recommendations on which Swedish computer terms to use, the Joint Group for Swedish Computer Terminology, JOGSCOT, was established in 1996. JOGSCOT includes national expertise both in computer technology and in terminology, general language planning, standardization and translation - a fäet which helps to pave the way for the recommendations given. Before. being published on the JOGSCOT web site, which is open and free of charge for all Internet users, the suggested recommendations are discussed mainly via e-mail. The MUS programme (Multilingual Information Society) of the the European Commission is now financing a project called WebIT/EFCOT. The EFCOT part of this project is based on the work carried out within JOGSCOT and aims at exporting its method of working to Finland, Norway and Greece. A second aim within EFCOT is to offer a European forum for discussions on computer terminology - to begin with as a joint web site, the EFCOT site.